Enantioselective Degradation of (2RS, 3RS)‐Paclobutrazol in Peach and Mandarin Under Field Conditions. Issue 8 (28th May 2014) - Wang, Xiangyun; Qi, Peipei; Yang, Guiling; Wang, Xinquan; Zhang, Hu; Xu, Hao; Wang, Zhiwei; Wang, Qiang
ABSTRACT In this study we investigated the enantioselective degradation of (2RS, 3RS)‐paclobutrazol in peach and mandarin fruits under field conditions after foliar treatment at 500 mg active ingredient/L using a Lux Cellulose‐1 chiral column on a reverse‐phase liquid chromatography–tandem mass spectrometry system. Degradations of paclobutrazol in both fruits followed first‐order kinetics, with half‐lives of about 9 days. Initial deposits were 1.63 mg/kg on peach and 1.99 mg/kg on mandarin; terminal concentrations were lower than 0.05 mg/kg, which was acceptable in most cases. As anticipated, paclobutrazol levels in peels of mature mandarin were about 6.3 times higher than in pulp, indicating the potential risk of peel consumption. We also observed that paclobutrazol degradation in mature mandarin was relatively slow, indicating it might not be efficient enough to hold mandarin fruits on trees for lowering paclobutrazol concentrations. Significant enantioselectivity was observed: the (2R, 3R)‐enantiomer was preferentially degraded in mandarin (whole fruit, peels, and pulp) but enriched in peach. Because of its more rapid degradation in mandarin and the lower levels observed in pulp compared with peels, potential endocrine‐related side effects due to the (2R, 3R)‐enantiomer pose less of a risk in mandarin than in peach. Chirality 26:400–404, 2014. © 2014 Wiley Periodicals, Inc.